Os hábitos da memória nos conflitos dos protagonistas de Menalton Braff em Que enchente me carrega? (2000) e Bolero de Ravel (2010) - Silva, Natali Fabiana da Costa e [UNESP] (2015)
This research has as corpus two novels of the contemporary writer Menalton Braff - Que enchente me carrega? (2000) e Bolero de Ravel (2010) and seeks to describe, amid the stream of consciousness that represents the thinking of the protagonists, an endless number of memories that are repeated from the beginning to the end of the stories: 13 memories are presented in Que enchente me carrega? and 15 memories in Bolero de Ravel. It is understood that the very structure of the narrative is established through repeated circularity of mnemonic processes present in the two works, setting the pace and consistency of the fictional text. Moreover, it is possible to observe that repetitions establish how the narrators look at the world around, determining what they see, how they perceive what they see and finally how they deal with what they perceive. The research considers that the repetitions in the novels is endowed with undeniable aesthetic intentionality and that it constitutes a characteristic of Braff's narrator. The narrator, when narrating his own process of social and mental decay, creates the image of his disengagement in the world. We named this procedure as the process of disintegration of the character. The thesis will be analyzed from the theoretical tools of the stream of consciousness, bringing to light the concepts proposed by Robert Humphrey and Belinda Cannone. This approach will include, at the same time, the historical processes that underlie the crises of the novel and the advent of the stream of consciousness fiction